Inter-relações entre as vivências musicais de jovens em diferentes contextos socioculturais e suas práticas musicais em um projeto sócio-orquestral - Souza, Leonardo da Silva (2020)
This work is the result of a master's research, which aimed to understand how the musical experiences of young people in different sociocultural contexts interrelate with the musical practices developed in one of the poles of the Inclusion Through Music and Arts Program (PRIMA); while its specific objectives sought to identify how musical experiences are present in the daily lives of young members of the teaching pole, as well as the means and sociocultural spaces from which these musical experiences occur; verify the practices performed by young people in the teaching pole or in the program more broadly; and analyze the interrelationships identified between their musical experiences in different sociocultural contexts and the musical practices developed in the context of the Program. Therefore, this research was developed from a case study, in which data were collected through a questionnaire, participant observation and semi-structured interview. Such techniques made it possible to monitor the activities developed by the students in the Program, as well as the collection of data regarding their experiences in other contexts. Five young people aged between 14 and 17 years participated in the research and the collection took place between the months of August and December 2019. The data analysis had as theoretical support the studies related to the Youth Condition; the Sociocultural Approach to Music Education and the Theories of Everyday Life in Music Education. As a result of the research, it was found that young people had diversified musical experiences that were presented through spheres such as: family, church and school; and that they established some interrelationships between the musical practices developed in the Program and these varied spheres, enabling a more specific educational-musical practice that was more connected with their own juvenile condition.